Contingent Valuation of Watershed Protection in Nigeria: A Case Study - Femi Olokesusi (Faculty of Geography, Universitas Gadjah Mada, 1994)
The search for appropriate methods for valuing natural resources and monctising externalities is a pressing problem facing many governments, particularly those of the developing countries. While the Nigerian government allocates 2% of its annual gross income for ecological damage restitution (The Ecological Fund), experiences arising from incessant disputes in the oil producing areas, fishing sites, increasing incidence of soil erosion and flooding and other environmental problems, all point to the need to supplement the Ecological Fund with money from other sources.Most environmental degradation resulting from mithropogenic prococcrs in water resource projects can be ascribed to the